Atomic force microscopy fishing and mass spectrometry identification of gp120 on immobilized aptamers - Ivanov YD (Dove Medical Press, 2014)
Yuri D Ivanov,1 Natalia S Bukharina,1 Tatyana O Pleshakova,1 Pavel A Frantsuzov,1 Elena Yu Andreeva,1 Anna L Kaysheva,1,2 Victor G Zgoda,1 Alexander A Izotov,1 Tatyana I Pavlova,1 Vadim S Ziborov,1 Sergey P Radko,1 Sergei A Moshkovskii,1 Alexander I Archakov1 1Department of Personalized Medicine, Orekhovich Institute of Biomedical Chemistry of the Russian Academy of Medical Sciences, Moscow, Russia; 2PostgenTech Ltd., Moscow, Russia Abstract: Atomic force microscopy (AFM) was applied to carry out direct and label-free detection of gp120 human immunodeficiency virus type 1 envelope glycoprotein as a target protein. This approach was based on the AFM fishing of gp120 from the analyte solution using anti-gp120 aptamers immobilized on the AFM chip to count gp120/aptamer complexes that were formed on the chip surface. The comparison of image contrasts of fished gp120 against the background of immobilized aptamers and anti-gp120 antibodies on the AFM images was conducted. It was shown that an image contrast of the protein/aptamer complexes was two-fold higher than the contrast of the protein/antibody complexes. Mass spectrometry identification provided an additional confirmation of the target protein presence on the AFM chips after biospecific fishing to avoid any artifacts. Keywords: gp120 HIV-1 envelope glycoprotein, aptamer, atomic force microscopy, mass spectrometry